Extending the Common Sense Model to Explore the Impact of Visceral Sensitivity on Quality of Life in Inflammatory Bowel Disease - Hayes, Bree; Burgell, Rebecca; Apputhurai, Pragalathan; Garg, Mayur; Knowles, Simon R. (Turkish Journal of Gastroenterology, 2022)
Background: Inflammatory bowel disease is associated with poor quality of life. The aim of the cross-sectional study was to extend the common sense model to explore the impact of inflammatory bowel disease activity on quality of life and the potential mediating roles of illness perceptions, visceral sensitivity, coping styles, acceptance, and psychological distress. Methods: A total of 141 inflammatory bowel disease patients (86 with Crohn’s disease and 55 with ulcerative colitis; 74 males, 65 females, and 2 gender non-specific, mean age 40.43 years) from 2 metropolitan hospital inflammatory bowel disease outpatient clinics participated. Measures included disease activity (Crohn’s Disease Activity Index, Simple Clinical Colitis Activity Index), illness perceptions (Brief Illness Perceptions Questionnaire), visceral sensitivity (Visceral Sensitivity Index), coping styles (Brief Coping Operations Preference Enquiry), acceptance (Acceptance and Action Questionnaire-II), psychological distress (Depression, Anxiety, and Stress Scale), and European Health Interview Survey-Quality of Life (EUROHIS-QoL). Results: A structural equation model of the extended common sense model was found to have a good fit (χ2(10) = 10.07, P = .43, root mean square error of approximation = 0.01, standardized root mean residual = 0.04, comparative index fit = 1.00, Tucker–Lewis index = 1.00, goodness-of-fit = 0.98). After controlling for irritable bowel syndrome diagnosis, the impact of disease activity on quality of life was statistically mediated by illness perceptions, maladaptive coping styles, and psychological distress. In addition, visceral sensitivity bordered on influencing the impact of disease activity and illness perceptions on quality of life through psychological distress. Conclusions: This study demonstrates that together with illness perceptions and coping styles, visceral sensitivity plays an important role in an individual’s adaption to living with inflammatory bowel disease. Cite this article as: Hayes B, Burgell R, Apputhurai P, Garg M, Knowles SR. Extending the common sense model to explore the impact of visceral sensitivity on quality of life in inflammatory bowel disease. Turk J Gastroenterol. 2022;33(2):103-110